2021
DOI: 10.21608/ejhm.2021.160053
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Practice and Nutritional Status Among Pregnant Women

Abstract: Background: Appropriate balanced maternal nutrition is the principal determinant for maternal and fetal wellbeing. Consequently, the dietary practice and nutritional status of pregnant ladies need to be addressed properly as it should follow the recommendations of the food pyramid. Objective: to assess dietary practice and nutritional status among pregnant women attending antenatal Care In the rural Family Health Unit. Methods: The study was a Facilitybased cross-sectional study conducted in the Terrene family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The current study also revealed that women whose partners’ education level of high school and above had higher appropriate dietary practice, which is consistent with the former studies done in Wachamo [ 36 ], and Shashamane [ 11 ]. This might be because literate partners have a better understanding of the importance of consuming a quality diet in pregnancy, and they may positively influence their wives to have appropriate dietary practices.…”
Section: Discussionsupporting
confidence: 92%
“…The current study also revealed that women whose partners’ education level of high school and above had higher appropriate dietary practice, which is consistent with the former studies done in Wachamo [ 36 ], and Shashamane [ 11 ]. This might be because literate partners have a better understanding of the importance of consuming a quality diet in pregnancy, and they may positively influence their wives to have appropriate dietary practices.…”
Section: Discussionsupporting
confidence: 92%
“…So, pregnant women should have educational sessions about the importance of breakfast. This is consistent with the results of Alkalash, Hegazy, ELnady& Khalil (2021)who stated that about two-thirty of the studied women ate three times per day. Also, near to half of them didn't delete the dinner meal.…”
Section: Discussionsupporting
confidence: 93%
“…Respondent age is a vital indicator of the nutritional status of pregnant women. Some previous studies revealed that respondent age during the third trimester of pregnancy is a risk factor for developing malnutrition [52,53]. The husband's age is also an important feature in the nutritional status of pregnant women.…”
Section: Plos Onementioning
confidence: 99%